THERAPEUTIC POTENTIALS OF ETHANOLIC EXTRACT OF LEAVES OF HOLARRHENA FLORIBUNDA (G. DON) DUR. AND SCHINZ (APOCYNACEAE) - Hoekou, Yao Patrick; Tchacondo, Tchadjobo; Karou, Simplice Damintoti; Yerbanga, Rakiswende Serge; Achoribo, Elom; Da, Ollo; Atakpama, Wouyo; Batawila, Komlan (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Holarrhena floribunda is a plant of wide usage in the Togolese folk medicine. A previous ethnobotanical survey on the latex plants of the Maritime region of the country revealed that this plant was included in several recipes curing malaria and microbial infections. Therefore, this study aimed to seek for the effectiveness of the ethanolic extract of the plant in the treatment of these diseases. Methods: The antimicrobial test was performed using the agar well-diffusion and the NCCLS broth microdilution methods, while the in vivo antimalarial activity was evaluated following the four-day suppressive test of Peters. The acute toxic effects of the extract were monitored after a single oral dose (5,000 mg/kg body weight) administration in NMRI mice. Results: The results indicated that the ethanolic extract of leaves of H. floribunda was active on Staphylococcus aureus ATCC 29213 and clinical strains of Staphylococcus aureus, Salmonella typhi and Klebsiella pneumoniae with MICs ranging from 0.62 to 1.25 mg/mL. The extract also showed significant parasitaemia suppression in a dose-dependent manner. In the acute toxicity assay, the oral administration of the extract to the mice did not affect the relative weight of vital organs, and there were no signs of toxicity or death during the study period. The LD50 of the tested extract was found to be greater than 5,000 mg/kg, indicating its safety. Conclusion: This study demonstrates the antibacterial and antimalarial activities of leaves of H. floribunda and then, supports its medicinal use in the treatment of microbial infections.